Azotobacter and Pseudomonas Population in Rhizosphere and Yield of Choy Sum following Chemical Fertilizer and Biofertilizer application - Reginawanti Hindersah; Nini Mila Rahmi (Agrologia, 2020)
The limestone hilly landscapes, well  known as karst hills, in Muna Island resulted in natural grow of cashew (Anacardium occidentale L.). The karst area alos  support the cultivation of local food crops such as maize. Both local products need to be maintained in order to increase the community's revenue and give the identity to Muna Island as cashew nuts and maize producer. Cashew and maize are the leading commodities of Muna Island. This article describes the cultivation conditions and economic value of cashew nuts and maize in Muna Island. However, to achieve optimal production and selling value, technology adoption either in the field or  post-harvest, needs to be improved especially for cashew.